Enrichment Mechanism of Rare Earth Elements in the Aluminum-bearing Rock Series of the Jinsha Area in Northwest Guizhou Province - Kun QIE; Yang LAI; Daxing GONG; Enyuan TIAN (Kuangchan zonghe liyong)
The rare earth element (REE) content in the aluminum-bearing rock series of the Lower Carboniferous Jiujialu Formation in the Jinsha Area of northwest Guizhou is relatively high, showing certain exploration potential. This paper studies the enrichment mechanism of REE in the aluminum-bearing rock series through field profile measurement, trench logging, core logging, microscopic identification, major and trace element, and REE chemical analysis. The results show that the ΣREE content in the aluminum-bearing rock series of the Jinsha Area in northwest Guizhou is relatively high, ranging from 156.31×10-6 to 1 543.70×10-6, with an average of 743.49×10-6. Light rare earth elements are relatively enriched, and the ΣLREE/ΣHREE value ranges from 2.20 to 10.69. The enrichment of REE in the aluminum-bearing rock series is influenced by multiple factors such as the content of clay minerals and iron-bearing minerals. Light rare earth elements have a higher hydrolysis rate at alkaline conditions and are easily enriched. An oxidized environment is conducive to the deposition of REE3+. The water body of the limonitic bauxite in the Jinsha Area is weakly alkaline, and the sedimentary environment is oxidized, providing favorable conditions for the enrichment of REE. The REE content in the high-iron limonitic bauxite at the bottom of borehole ZK01 ranges from 0.115% to 0.150%, indicating that the aluminum-bearing rock series in the Jinsha Area has great exploration potential for REE.